ACT-13 RESPONSE TO SEIZURE AND TUMOR-PROGRESSION BY TREATMENT WITH PERAMPANEL IN PATIENTS WITH GLIOMAS. (16th December 2019) - Izumoto, Shuichi; Miyauchi, Masaru; Watanabe, Akira; Murakami, Saori; Tsuyuguchi, Naohiro; Kato, Amami
Abstract: BACKGROUND: Increased extracellular glutamate level activates AMPA type glutamate receptors (AMPA-receptor) and induces seizures. Antagonistic activation of AMPA-receptors inhibits epilepsy and glioma progression in vivo and in vitro studies. PATIENTS AND METHODS: (1) We tested perampanel (PER), an AMPA-receptor antagonist, in fifteen glioma patients with uncontrolled epilepsy. Seizure response, PER concentration, and tumor volume were assessed. (2) We tested PER in thirteen glioma patients (gr 2- 3 cases, gr 3- 4 cases, and gr 4- 4cases) after the initial treatment of surgery and RT (and CT). RESULTS: (1) An objective seizure response was observed in 13 analyzed patients (100%) with 8 cases (62%) of seizure-freedom. Median plasma concentration of PER was 232 ng/ml in patients with 4mg/day PER and 518 ng/ml in patients with 8mg/day PER. High intensity lesions of MRI-FLAIR images were assessed volumetrically to analyze the tumor size. The volume reduction was detected during the 6 months period in correlation with the plasma PER levels. (2) All the 13 cases treated with PER after the initial treatment was seizure free. Two cases of gr 4 were died at 18 and 20 months after the surgical treatment. Other 11 cases are survival-free. CONCLUSION: PER treatment was effective in uncontrolled epilepsy with gliomas. MRI images showed the inhibition of tumor-progression. PER may effective for the inhibition of tumor progression.